Incentivos e riscos no desempenho de fundos: o impacto do ranking na manipulação do risco pelos gestores - Elmo Henrique de Moraes (2008)
The mutual fund industry deals with a great competitivity in what concerns keeping and maintaining the clients and getting new resources. In order to achieve these goals, one of the most important aspects is to present a satisfying level of profit in relation to the opponents.Based on what performance were, in terms of a profit ranking, the managers change the portfolios composition, even increasing the risk, in order to get a better result, and by that, to achieve better conditions to attract new investments and reward. This thesis, based on quantityand observation, proposes to verify if there is any relation between the result in a certain period and the strategy of the manager in relation to the risk taken in the following periods. The analysis using tournament theory was made based on the Multimercados funds in the Brazilian market between 2002 and 2007 finding that the looser portfolio managers arewilling to manipulate the risk in a different way than the winner, and in some periods, under certain characteristics, even assuming more risk.